Optymalne kształtowanie kratownic przy uwzględnieniu warunków stateczności - Wojdanowska-Zając, R.; Życzkowski, M. (Engineering Transactions, 1969)
In the paper the optimal configuration has been determined of four truss systems, presented in Fig. 1, 5, 8 and 11. As a criterion of design the minimal volume (weight) was assumed, and as auxiliary conditions either the conditions of strength and stability of the individual bars compressed in the elastic range, or the condition of elastic-plastic stability for compressed bars and the condition of strength for stretched bars. In the elastic range the method of transformationlinearizing auxiliary conditions was utilized, given by W. Krzyś and M. Życzkowski in paper (22), In the inelastic range the critical force was determined by the universal formulae of A. Ylinen, which enable the uniform notation in the entire interval of slenderness ratio considered. The results have been presented either in explicit form or implicit or parametrical form, and moreover have been graphically illustrated, making the optimal angles of inclination of the bars dependent on the parameter of slenderness ratio of the truss.